Targeting fibroblast-like synovial cells at sites of inflammation with peptide targeted liposomes results in inhibition of experimental arthritis - Vanniasinghe, A S (Clinical immunology (Orlando, Fla.), 2014)
Copyright © 2014 Elsevier Inc. All rights reserved.